Poverty and welfare measurement on the basis of prospect theory - Markus Jäntti; Ravi Kanbur; Milla Nyyssölä; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper examines the measurement of social welfare, poverty and inequality taking into account features that have been found to be important welfare determinants in behavioural economics. Most notably, we incorporate reference-dependence, loss aversion and diminishing sensitivity - aspects emphasized in prospect theory - to social welfare measurement. We suggest a new notion of equivalent income, the income level with which the individual would be as well off, evaluated using a standard concave utility function, as he or she actually is, evaluated with a reference-dependent utility function. We examine the differences between standard poverty and inequality measures based on observed income and measures that are calculated based on equivalent income. These differences are illustrated using household-level panel data from Russia and Vietnam.
Keywords: I32; O12; 330; prospect theory; poverty; inequality; welfare measurement; vulnerability; Soziale Wohlfahrtsfunktion; Messung; Armut; Disparitätsmaß; Prospect Theory; Theorie; Russland; Vietnam